Long term post-traumatic stress disorders among the earthquake affected people of Sindhupalchwok, Nepal - Gautam, Laxmi; Mishra, Durga Khadka; Pant, Gobind Prasad; Khadka, Rabina; Chataut, Prakash Datt; Shrestha, Tripti; Thapa, Sailendra (International Journal Of Community Medicine And Public Health, 2021)
Background: People who are suffering from PTSD have disturbing feelings and thoughts which is related to their experience even after a long time of such traumatic events happened. This study highlight the characteristics and prevalence of PTSD among the earthquake survivors. Methods: Cross sectional study was carried out using standard PCL-5 PTSD questionnaire. Interview was taken among 376 survivors of earthquake after 4 years of earthquake in Sindhupalchok. Descriptive statistics, Chi-square test and multiple logistic regression were used to describe data and test association. Results: The mean age of the respondents was 39.47±16.18 years. Almost 2/5th of the respondents were either buried, injured or physically or mentally disabled during earthquake. Majority of the survivors had loss their loved one while most of them loss their property. Among the respondents who were buried 28.6% had develop PTSD which was 22.2% among physical or mental disable during earthquake. PTSD showed significant association with age, loss of known person and loss of property however didn’t show with gender, caste, experience of earthquake and so on. The prevalence of PTSD was 71 (21.5%) out of 331 respondents. Female (63.4%) were more prone to PTSD than male (36.6%). Conclusions: PTSD is prevalent among 21.5% of survivors even after 4 years of earthquake which showed an urgent need to address PTSD among the respondents and immediate intervention to prevent and treat such problems in case of future disasters.